2021
DOI: 10.18186/thermal.889174
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Rectangular Pin-Fin Heat Sink Subject to an Impinging Air Flow

Abstract: The heat sink is used to enhance heat rejection from heated surface to air. The seize and the geometry of the heat sink with the shape of the extended surfaces have a great influence on the heat transfer coefficient. The first step to get the optimal design is to predict the heat transfer by conduction in solid walls of heat sink and then by convection between the solid and air flow. The purpose of the present study is to predict the effectiveness of closely spaced parallel rectangular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Naphon and Wongwises [28] investigated the effect of jet impingement cooling by observing the working temperature of a CPU and observed comparatively lower temperatures. Mohammed and Razuqi [29] studied effects on heat transfer coefficient for a rectangular pin fin heat sink subjected to jet impingement. They concluded that with an increase in the Reynolds number, the thermal resistance decreased, which in turn led to an increase in the average Nusselt number.…”
Section: Use Of Extended Surfaces (Fins)mentioning
confidence: 99%
“…Naphon and Wongwises [28] investigated the effect of jet impingement cooling by observing the working temperature of a CPU and observed comparatively lower temperatures. Mohammed and Razuqi [29] studied effects on heat transfer coefficient for a rectangular pin fin heat sink subjected to jet impingement. They concluded that with an increase in the Reynolds number, the thermal resistance decreased, which in turn led to an increase in the average Nusselt number.…”
Section: Use Of Extended Surfaces (Fins)mentioning
confidence: 99%